"I'll be more prepared than most people": Very young Canadian workers talking about their first jobs. (May 2018) - Raby, Rebecca; Lehmann, Wolfgang; Easterbrook, Rachel; Helleiner, Jane
We report on interviews with very young Canadian workers regarding their first jobs, with a focus on why they started working, the rewards and risks of their work, and their familial supports. Our participants were largely positive about their early work experiences, although they also raised concerns, e.g. about safety. We reflect on three inter-related themes emerging from their accounts: competence and vulnerability, independence and dependence, and protection and under-protection.